Keridhaan (Antaradhin) Dalam Jual Beli Online (Studi Kasus UD. Kuntajaya Kabupaten Gresik) - Ardhinata, Ahliwan; Fanani, Sunan (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
The purpose of this study was to determine whether the implementation of the sale and purchase agreement online istishna applied by Mr. H. Fiter Kuntajaya there has been no good pleasure.The research method used is a qualitative approach with descriptive case study. The case study is a qualitative research trying to find meaning, to investigate the process and gain a deep insight and understanding of individual, group, or situation. Data collection was conducted by interviewing informants in this study is the owner of UD. KUNTAJAYA. In addition, interviews were also conducted with several other informants as a consumer as a process of triangulation.The result is the application of the sale and purchase agreement online istishna based in accordance with the rules of Islamic purchase made by H. Fiter Kuntajaya against consumers it did not affect the consumer to fully understand the applicable contract. However, the implementation of online trading Fiter H. Kuntajaya implement trading system in accordance with the rules of Islamic jurisprudence purchase turned out to fruition in the form of the pleasure of the consumers, so that consumers who had dealings with H. Fiter Kuntayaja feel comfortable, satisfied and loyalty arise in transaction.